Prostaglandin E2 confers protection against diabetic coronary atherosclerosis by stimulating M2 macrophage polarization via the activation of the CREB/BDNF/TrkB signaling pathway. Issue 6 (29th April 2020) - Bi, Changlong; Fu, Yili; Zhang, Zheqi; Li, Bo
Abstract: It has been documented that M2 macrophage polarization plays a suppressive role in atherosclerosis in diabetes mellitus (DM). In addition, prostaglandin E2 (PGE2) is implicated in the development of M2 macrophage polarization. Therefore, the study aimed to investigate the specific mechanism of PGE2 in M2 macrophage polarization in diabetic coronary atherosclerosis (DMAS). Initially, clinical samples were obtained and DMAS mouse model was established. The expression of BDNF was determined, and M1 and M2 macrophage polarizations were evaluated. Then, the levels of BDNF and PGE2 were modified in DMAS mice and the serum indicator, atherosclerotic plaque, lipid uptake by PBMCs, as well as M1 and M2 macrophage polarization were determined. Macrophages were isolated and the effects of PGE2 and the CREB/BDNF/TrkB signaling pathway on M2 macrophage polarization were explored. BDNF was downregulated and macrophages were differentiated into M1 in DMAS patients and mice. BDNF and PGE2 were observed to promote M2 macrophage polarization, where atherosclerotic plaque and lipid uptake by PBMCs were reduced, and DMAS was alleviated in mice. Overexpression of BDNF activated the CREB/BDNF/TrkB signaling pathway and stimulated M2 macrophage polarization in macrophages. PGE2 stimulated M2 macrophage polarization by inducing KLF4 via the activation of the CREB/BDNF/TrkB signaling pathway. This study demonstrates that PGE2 promotes M2 macrophage polarization by activating the CREB/BDNF/TrkB signaling pathway, thus alleviating DMAS.